2022
DOI: 10.3390/ijms23126626
|View full text |Cite
|
Sign up to set email alerts
|

PARK7/DJ-1 as a Therapeutic Target in Gut-Brain Axis Diseases

Abstract: It is increasingly known that Parkinson’s (PD) and Alzheimer’s (AD) diseases occur more frequently in patients with inflammatory gastrointestinal diseases including inflammatory bowel (IBD) or celiac disease, indicating a pathological link between them. Although epidemiological observations suggest the existence of the gut-brain axis (GBA) involving systemic inflammatory and neural pathways, little is known about the exact molecular mechanisms. Parkinson’s disease 7 (PARK7/DJ-1) is a multifunctional protein wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…DJ-1-deficient microglia leads to a further increase in inflammatory cytokine release. Thus, abnormal DJ-1 function leads to accelerated disease progression in Parkinson's disease (Sliter et al, 2018;Neves et al, 2022;Pap et al, 2022; Figure 2).…”
Section: Microglia and Parkinson's Diseasementioning
confidence: 99%
“…DJ-1-deficient microglia leads to a further increase in inflammatory cytokine release. Thus, abnormal DJ-1 function leads to accelerated disease progression in Parkinson's disease (Sliter et al, 2018;Neves et al, 2022;Pap et al, 2022; Figure 2).…”
Section: Microglia and Parkinson's Diseasementioning
confidence: 99%
“…These small-molecule drugs can be future divided into two categories, based on their potency in targeting DJ-1’s enzymatic/catalytic activities and/or non-enzymatic activities (that is to say, structural activities). Overall, the pharmaceutical or genetic activation/suppression of DJ-1 in combination with other therapies (such as immuno-oncology) will open up new avenues for the treatment of various intractable human diseases other than cancer and PD (such as gut–brain axis diseases and ischemia–reperfusion injury) [ 87 , 88 ].…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…With the deepening of study, it has been found that PARK7/DJ-1 can regulate almost all neuroinflammatory diseases. According to the experimental data, PARK7/DJ-1 alleviates the condition of AD by reducing the activity of glyoxalase activity and reducing the harmful effects on neurons ( Pap et al., 2022 ). It is reported that the decrease in the expression of PARK7/DJ-1 induces an inflammatory response in colon cancer cells, indicating its anti-inflammatory effect ( Lippai et al., 2021 ).…”
Section: Innate Immune Signaling Pathway Regulates Inflammatory and I...mentioning
confidence: 99%
“…It is reported that the decrease in the expression of PARK7/DJ-1 induces an inflammatory response in colon cancer cells, indicating its anti-inflammatory effect ( Lippai et al., 2021 ). Similarly, PARK7/DJ-1 affects the local and systemic inflammatory characteristics of IBD by maintaining gut microbiome and mucosal integrity ( Pap et al., 2022 ). In addition, through the proteomics detection of the plasma of IBD patients, it was found that the PARK7/DJ-1 protein in plasma increased ( Di Narzo et al., 2019 ).…”
Section: Innate Immune Signaling Pathway Regulates Inflammatory and I...mentioning
confidence: 99%